Frost damage on grain number in wheat at different spike developmental stages and its modeling - Martino, Diana Laura; Abbate, Pablo Eduardo (Elsevier, 2019)
Frosts may damage wheat (Triticum aestivum L.) spikes and severely reduce their yield. The objective of this study was (i) to quantify the level of susceptibility to frost at different spike developmental stages, and (ii) to develop a theoretical-empirical model to estimate successive frosts damage on grain number (GN) at different spike and crop developmental stages based on the meteorological characteristics of the event. Three experiments were performed under field conditions at Balcarce (Argentina), using Klein Roble and Floripan 100 spring cultivars, sown on seven dates. The proportion of aborted grains in spikes was evaluated at different spike developmental stages, from stem elongation to the beginning of grain filling, with all spikes receiving the same natural frosts. The higher the frost severity (defined as the number of hours with temperatures <-1.5 °C and the minimum temperature reached), the higher the damage on GN (28 to 88%, depending on the experiment). The duration of the period in which maximum damage on GNwas registered was variable, but it always included anthesis. Based on collected data, a theoretical-empirical model to estimate successive frosts damage on GN at different spike or crop developmental stages was proposed and validated. This study provides a detailed quantification of the damage caused by natural frosts under field conditions and it allows to achieve a better estimation of frost effect on crop.